Aerobic Oxidation of Benzylic Carbons Using a Guanidine Base - Lee, Seulchan; Kim, Si Ae; Jang, Hye Young (ACS Omega, 2019)
Metal-free reaction conditions featuring oxygen and 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) were employed for the selective oxidation of benzyl amines and active methylene compounds to afford various amides and ketones. Owing to the strong basicity of guanidine bases, TBD is presumed to play an important role in the cleavage of the C-H bond at the benzylic position of peroxide intermediates, which were formed by the reaction with oxygen.